2019
DOI: 10.1155/2019/7697610
|View full text |Cite
|
Sign up to set email alerts
|

TEEG Induced A549 Cell Autophagy by Regulating the PI3K/AKT/mTOR Signaling Pathway

Abstract: TEEG (3β,16β,23-trihydroxy-13,28-epoxyurs-11-ene-3-O-β-D-glucopyranoside) is derived from the chloroform extract of the Chinese medicine formula Shenqi San (CE-SS). In the present study, we aimed to elucidate the anticancer effect and possible molecular mechanism underlying the action of TEEG against the human non-small cell lung cancer (NSCLC) cell line A549 in vitro. A549 cells were incubated with different concentrations of TEEG. Cell proliferation was assessed by MTT assay. Autophagy was evaluated by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…These findings suggest that CypA can protect A549 cells from H2O2induced oxidative injury and apoptosis.In many cancers, including lung carcinoma, the PI3K/AKT/mTOR pathway is hyperactive, thus blocking apoptosis through the regulation of downstream signaling molecules, such as inhibiting the activation of Caspase-7, as well inactivating Bcl-2 family members[50,51]. Emerging evidence has demonstrated that activation of the PI3K/Akt signaling pathway protects A549 cells from oxidative stress and apoptosis[52][53][54]. Intriguingly, a previous study reported that extracellular CypA promotes platelet adhesion via cluster of differentiation 147 (CD147)-mediated PI3K/Aktsignaling[55].…”
mentioning
confidence: 99%
“…These findings suggest that CypA can protect A549 cells from H2O2induced oxidative injury and apoptosis.In many cancers, including lung carcinoma, the PI3K/AKT/mTOR pathway is hyperactive, thus blocking apoptosis through the regulation of downstream signaling molecules, such as inhibiting the activation of Caspase-7, as well inactivating Bcl-2 family members[50,51]. Emerging evidence has demonstrated that activation of the PI3K/Akt signaling pathway protects A549 cells from oxidative stress and apoptosis[52][53][54]. Intriguingly, a previous study reported that extracellular CypA promotes platelet adhesion via cluster of differentiation 147 (CD147)-mediated PI3K/Aktsignaling[55].…”
mentioning
confidence: 99%
“…Meanwhile autophagy provides nutritional support to cells under different stress conditions and is regarded to be one of the physiological processes that can affect cell survival [30]. Autophagy in lung cancer can be inhibited by oncogenes, such as PI3K and mTOR, while it can be activated by autophagy-related proteins, such as ATG5, ATG12 and Beclin-1 [31]. In our work, after the treatment of PX-866 and PI-103, the expression of ATG5, ATG12 and Beclin-1 in CCRF-CEM and Jurkat cells was dramatically elevated.…”
Section: Discussionmentioning
confidence: 99%